Tannic acid crosslinking in Tilapia gelatin microfibers produced by Solution Blow Spinning - Vilches, José Luiz [UNESP]; Martin, Cibely da Silva [UNESP]; Sanches, Alex Otávio [UNESP]; Malmonge, José Antonio [UNESP] (Elsevier, 2025)
Developing microfibers from fish gelatin (FG) is important due to its potential as a sustainable and biocompatible material, making it valuable for applications in packaging, as well as in technological and biomedical fields. This study investigates the formation of membranes derived from Nile tilapia (Oreochromis niloticus) gelatin incorporating tannic acid (TA). Membranes were successfully produced using electro-assisted solution blow spinning (E-SBS) technology. The samples were characterized in terms of morphology, water stability, thermal properties and scavenging activity. The results indicate that applying an electrical voltage of 3 kV between the needle and the collector enabled the production of microfibers with a diameter of 276 ± 81 nm, approximately 67 % thinner than those produced without the applied electric field. The incorporation of 3 % TA, relative to the mass of FG, resulted in a 218 % increase in membrane integrity in water compared to the membrane without TA, ascribed to crosslinking via hydrogen bonding. Thermal analyses revealed that the membranes incorporated with TA maintain thermal stability at temperatures below 150 °C, and through X-ray diffractograms reveal low molecular order as observed in neat gelatin membrane. The gelatin membrane with 20 % TA exhibited 90 % DPPH• radical scavenging activity within 10 min, outperforming gelatin-only membranes. These findings suggest that TA-crosslinked gelatin membranes have significant potential for technological applications, particularly in fields requiring greater stability in wet environments and antioxidant activities, such as food packaging.
Keywords: Gelatin microfiber; Nile tilapia; Solution Blow Spinning; Tannic acid